Sustainability Analysis of Social Interactions Achieved by Collaborative learning Resulted from NPTEL SWAYAM Mentor Scheme - Kulkarni, Vinay; Wakode, Jaya; Patil, Ashwini; N, Mrinalini; Deshmukh, Rutuja; Malathi, P (Journal of Engineering Education Transformations, 2025)
The NPTEL SWAYAM mentor scheme is an innovative initiative aimed at enhancing educational experience through collaborative learning and mentorship. This study conducts an impact analysis of social interactions facilitated by the scheme, focusing on its effectiveness fostering collaborative learning environments and improving student outcomes in higher education relevant to SDG 4. The research combines quantitative data from student performance metrics with qualitative insights from surveys and interviews conducted with participants, including mentors and mentees. The study evaluates how structured mentorship and peer interactions withing the scheme contribute to academic performance, social skills development and overall student engagement. Primary findings suggest that the mentor scheme significantly enhances collaborative learning by providing a structured environment where students can engage in meaningful interactions with peers and mentors. These interactions are shown to improve abilities of problem solving, critical thinking and communication skills amongst students. Furthermore, the sense of community and support fostered by the mentor scheme contributes to increased motivation and a positive learning experience. The research identifies key factors that influence the success of the collaborative learning process, such as the quality of mentor-mentee relationships, the effectiveness of communication channels, and the availability of resources on the SWAYAM platform. Challenges such as varying levels of mentor engagement and the need for continuous mentor training are also discussed. The research concludes with recommendations for optimizing schemes, including strategies for sustaining mentor training, improving digital tools for collaborations, and integrating feedback mechanisms to continuously refine the mentorship process. The findings underscore the potential of mentorship and collaborative learning frameworks in transforming educational practices and highlight the broader implications for integrating such schemes into digital learning platforms globally.